Short Communication: Intraspecific genetic diversity and population subdivision of rabbitfish (Siganidae: Siganus canaliculatus) in urbanized reefs of Jakarta Bay, Indonesia - Hawis Madduppa; MUTIARA KRISTINA MARGARETHA; ADITYA BRAMANDITO; TRI PRARTONO; BEGINER SUBHAN; DONDY ARAFAT; NURLITA PUTRI ANGGRAINI (Society for Indonesian Biodiversity, 2019)
Abstract. Madduppa H, Margaretha MK, Bramandito A, Prartono T, Subhan B, Arafat D, Anggraini NP. 2019. Short Communication: Intraspecific genetic diversity and population subdivision of rabbitfish (Siganidae: Siganus canaliculatus) in urbanized reefs of Jakarta Bay, Indonesia. Biodiversitas 20: xxxx. Indonesian coral reefs and seagrass are heavily influenced by human activities through pollution and habitat loss, and sea-level rise or the increase of ocean temperature due to the global change. In the Jakarta Bay and Seribu Islands, marine communities have been impacted by an increase in eutrophication and sedimentation levels. As a result, these habitats became degraded and could affect their associated organisms such as rabbitfish. Genetic diversity and population structure can provide information about a long-term condition in an aquatic organism. The study was conducted to assess genetic diversity and population structure of rabbitfish (Siganus canaliculatus) across an environmental gradient in Jakarta Bay and Seribu Islands. A total of 31 individuals were collected using gillnet in study sites. A molecular marker mitochondrial Cytochrome oxidase 1 (CO1) was used to amplify DNA. The result of the phylogenetic tree formed two major clades, which generally separate northern and southern region of Seribu Islands populations. AMOVA analysis showed significant genetic differentiation between the population of Siganus canaliculatus in the north zone (National Park) and south zone Seribu Island (FST = 0.38, p<0.005). The highest haplotype diversity (Hd) of Siganus canaliculatus contained was observed in the north (Pulau Semak Daun) and south (Pulau Damar) in both as moderate (0.50). Nucleotide diversity ( ) of Siganus canaliculatus was categorized as low (0.076) to moderate (0.500). Environment and humans seem to affect the value of genetic diversity, and as the study suggests, a significant population subdivision makes this population vulnerable.